2001
DOI: 10.1108/eum0000000006098
|View full text |Cite
|
Sign up to set email alerts
|

Relationship benefits in service industries: a replication in a Southeast Asian context

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
1
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(171 citation statements)
references
References 27 publications
6
155
1
9
Order By: Relevance
“…Western 'heartless' objectivity applied to this Thai business context could have meant sacrificing a long-term business relationship for a short-term gain. A similar orientation was identified in Patterson and Smith's (2001) study on relationship benefits in service industries. Thai consumers were found to be loyal to serviceproviders because of a perceived Bunkhun relationship which guarantees them special treatment if needed.…”
Section: Business Perspectives From Thailandsupporting
confidence: 66%
“…Western 'heartless' objectivity applied to this Thai business context could have meant sacrificing a long-term business relationship for a short-term gain. A similar orientation was identified in Patterson and Smith's (2001) study on relationship benefits in service industries. Thai consumers were found to be loyal to serviceproviders because of a perceived Bunkhun relationship which guarantees them special treatment if needed.…”
Section: Business Perspectives From Thailandsupporting
confidence: 66%
“…Prior research has shown that relational benefit is an antecedent to building a long-term relationship [25,31]. Relational benefits refer to the benefits that customers receive from long-term relationships above and beyond the core product or service performance [25].…”
Section: Relational Benefitsmentioning
confidence: 99%
“…As Homans (1950) argued, trust is produced through a gradual process of interpersonal interaction. In IBSE, a customer can directly communicate with the service providers, and so the dyad is more likely to communicate the mutual intention (Patterson and Smith, 2001). There are a number of IBSE between the service provider and the customer, including various series of moments of truth.…”
Section: Insert Figure 1 Herementioning
confidence: 99%
“…For instance, one measure was obtained by the following question "In service process, my needs would be fulfilled by the technological equipment such as Internet and ATM". To operationalize the relationship benefit, we used 11 items that sought to evaluate various relationship benefits, which was adapted from scales developed and validated by Gwinner et al (1998), Hennig-Thurau et al (2002), and Patterson and Smith (2001). Special treatment benefit and confidence benefit both included four items, respectively.…”
Section: Data Collection and Measuresmentioning
confidence: 99%